Business Internationalization Strategy Process Review Based on the Uppsala Model - Pahrizal, P.; Sudarmiatin, S.; Sumarsono, Hadi (Manunggal Halim Jaya, 2024)
Research on the process of business internationalization strategy has attracted the attention of researchers around the world. These various reviews in the business internationalization strategy process have attracted researchers to analyze its behavior and influencing factors with various theoretical approaches to contribute to the development of international business studies. This paper is intended to provide an overview of the various approaches applied in various business internationalization strategy processes. Small and Medium Enterprises (SMEs) have played an active role in economic development for various countries. Not only do they have an impact on the local market but also on the international market. The involvement of small and medium-sized enterprises businesses in the international world has brought great contributions to the country's economic development, employment, and exports. This paper reviews the studies and research that have been conducted by experts on the internationalization process for SMEs at different economic levels. It finds that there are some similar and different factors that play a role in the internationalization process, i.e. the classification of theories and methods that have been used in the research from the findings of previous studies. This review will provide a better understanding of the field of business internationalization strategy process.